2019
DOI: 10.1186/s12913-019-4595-y
|View full text |Cite
|
Sign up to set email alerts
|

Using concept mapping to inform the development of a transitional reintegration intervention program for formerly incarcerated people with HIV

Abstract: BackgroundAccessing HIV-related care is challenging for formerly incarcerated people with HIV. Interventions informed by the perspectives of these individuals could facilitate engagement with care and address competing priorities that may act as barriers to this process.MethodsWe used concept mapping to identify and prioritize the main obstacles to engaging with HIV-related care following prison release. In brainstorming sessions, formerly incarcerated people with HIV generated responses to a focused prompt re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The final concept map, on average, had seven clusters. Seven studies included reports of the peer-review process [31][32][33][34][35][36][37]. The authors of one study indicated that they followed a reporting guideline when preparing their manuscript [38].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The final concept map, on average, had seven clusters. Seven studies included reports of the peer-review process [31][32][33][34][35][36][37]. The authors of one study indicated that they followed a reporting guideline when preparing their manuscript [38].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Concept mapping has been employed in several settings, including domestic violence, end-of-life initiatives, and substance use (Crawford-Browne & Kaminer, 2012 ; Rao et al, 2005 ; Windsor, 2013 ). Of the concept mapping studies related to substance use and criminal legal involvement, each focuses on only one of these topics or a different connection (e.g., incarceration and HIV) (Antoniou et al, 2019 ; Pauly et al, 2022 ; Urbanoski et al, 2020 ). It is, however, underutilized in understanding the relationship between criminal legal involvement and overdoses.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding these gaps, a handful of cluster analytical approaches conducted to date offer some preliminary insights. First, hierarchical cluster analysis has demonstrated the need for trauma-informed services among formerly incarcerated people living with HIV [ 31 ]. Second, cluster analytic approaches used in combination with binary logistic regression identified a sub-cluster of individuals in the criminal legal system deemed to be frequent systems utilizers at high risk of reincarceration, with a shared risk profile of higher numbers of homeless episodes, rates of bipolar disorder and depression, and felony convictions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%